2019
DOI: 10.1007/s11136-019-02114-y
|View full text |Cite
|
Sign up to set email alerts
|

ICECAP-O, the current state of play: a systematic review of studies reporting the psychometric properties and use of the instrument over the decade since its publication

Abstract: Purpose A paper reporting the development of the ICECAP-O was published in 2006. Since then, there has been increasing interest in the use of capability-based measures within health economics and the ICECAP-O has been suggested for use in economic evaluation by decision-making bodies in the Netherlands and UK. Methods A systematic review of studies published between January 2006 and October 2018 which have assessed the psychometric properties of ICECAP-O or utilised the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 59 publications
3
46
0
Order By: Relevance
“…Capability measures may better capture these benefits compared to HRQL outcomes. The ICECAP-O [15] measures this construct in older adults, but it has not been used in a cataract patient population [16]. The ICECAP-O's five domains cover attachment (love and friendship), security (thinking about the future without concern), role (doing things that make you feel valued), enjoyment and control (independence).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Capability measures may better capture these benefits compared to HRQL outcomes. The ICECAP-O [15] measures this construct in older adults, but it has not been used in a cataract patient population [16]. The ICECAP-O's five domains cover attachment (love and friendship), security (thinking about the future without concern), role (doing things that make you feel valued), enjoyment and control (independence).…”
Section: Introductionmentioning
confidence: 99%
“…Brazier et al [20] recommend that a PBM is chosen based on the psychometric performance (including construct validity and responsiveness) in the patient population. Whilst the EQ-5D has been used in a cataract population before [18,21], there is currently no published evidence of the use of the ICECAP-O [16]. The objective of this analysis was to evaluate the construct validity and responsiveness of the EQ-5D-3L, EQ-5D-5L, EQ-5D-3L + VIS and ICECAP-O in a cataract patient population.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the ICECAP-O recommended by NICE is targeted at a subgroup of the population (older adults), whilst the ASCOT was specifically developed for the assessment of social care interventions. A recent review of the literature examined current trends in the application of ICECAP-O [11]. The authors found that the ICECAP-O has mainly been included as a secondary economic measure and the reporting of results is brief with minimal detail and often no discussion or interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…ASCOT can be used to generate the social care equivalent of the QALY (Bulamu et al, 2015;Makai et al, 2014). Another generic tool is ICECAP for older people, based on a capability approach (Coast et al, 2008), which is particularly suitable for people without or with only mild social care needs (Proud et al, 2019).…”
Section: Discussionmentioning
confidence: 99%